Reducing postoperative complications and improving clinical outcome: Enhanced recovery after surgery in pancreaticoduodenectomy – A retrospective cohort study. (March 2017) - Dai, Juntao; Jiang, Yongjian; Fu, Deliang
Abstract: Background: An enhanced recovery after surgery (ERAS) programme aims to reduce the stress response to surgery and thereby accelerate recovery. The experience of implementing the ERAS programmes in pancreatoduodenectomy (PD) is relatively limited. The aim of this study was to evaluate the feasibility, safety and clinical outcomes of the ERAS programme after PD at a high-volume Chinese university referral centre. Methods: Between September 2014 and July 2016, a retrospective analysis of 166 consecutive patients who underwent PD at a tertiary referral care center was carried out. Ninety-eight patients who received conventional perioperative management (the conventional group) were compared with 68 patients who received ERAS programme (the ERAS group). The incidences of postoperative complications, length of stay, expenses, postoperative readmissions, and reoperation rates were compared. Results: A total of 166 patients who underwent PD were analysed (68 patients in the ERAS group, and 98 patients in the conventional group). There were no significant differences in mortality, reoperation, and readmission rates. The ERAS group had a lower morbidity rate than the conventional group (50% vs. 90.8%; P = 0.00), as well as a shorter length of hospital stay (7.5 vs 12 days; P = 0.00). Delayed gastric emptying was significantly reduced in the ERAS group (0 vs. 11.2%; P = 0.011). Pancreatic fistula (grade B, C) was significantly reduced in the ERAS group (14.7 vs 30.6%; P = 0.018). The median total hospital cost was also significantly reduced in the ERAS group (¥79790.40 vs ¥102982.81; P = 0.000). Conclusion: The ERAS programme is feasible and safe in patients who underwent PD, and it can reduce postoperative complications and improve clinical outcomes. Highlights: This study showed that implementation of ERAS program following PD was feasible and safe. The ERAS programme reduced LOS, DGE, pancreatic fistula (grade B, C), overall morbidity and total hospital costs without affecting reoperation, readmission, and mortality rates.